The Regionalism of Borders in Indonesia (Case Study: Sebatik Island, Indonesia) - Nugroho, Agung Satriyo; Rijanta, R; Santoso, Purwo; Marfai, Muh Aris (Indonesian Journal of Geography, 2023)
Border  management  has,  on  the  one  hand,  grown  beyond  the  conceptual  limit  that  is  the terminological deﬁnition of borders as lines separating countries to also factor in their development as areas. On the other, it should aim to strengthen state sovereignty and improve the welfare of its citizens. Tese ofen lead to the dichotomy between security and prosperity in border management approaches. Regionalism is an approach used to create regional integration across national borders, but this concept is strongly inﬂuenced by  the  interests  of  states  on  each  side  of  the  border.  Terefore,  this  research  explores  if  spatial  interaction between border communities is controlled by the regionalism concept introduced by the state or, instead, grows organically  as  part  of  regionalization  due  to  livelihoods  that  require  border  crossings.  It  used  a  case  study of Sebatik Island in the Indonesia-Malaysia border area. Te qualitative research design applied exploratory principles on the spatial interaction pattern formed between border communities and then synthesized the identiﬁed  units  of  information  on  transboundary  activities  while  considering  government-issued  policies on border management. Results showed that regionalism was only minimally implemented in managing the border  area.  It  means  that  border  landscapes  in  Indonesia  are  organically  formed  on  the  micro-scale  even though the perspective of regionalism has long been adopted at the regional level, i.e., ASEAN.